Proceedings of the EuroSun 2010 Conference 2010
DOI: 10.18086/eurosun.2010.06.24
|View full text |Cite
|
Sign up to set email alerts
|

Load Matching and Grid Interaction of Net Zero Energy Buildings

Abstract: Abstract"Net Zero Energy Building" has become a prominent wording to describe the synergy of energy efficient building and renewable energy utilization to reach a balanced energy budget over a yearly cycle. Taking into account the energy exchange with a grid infrastructure overcomes the limitations of seasonal energy storage on-site. Even though the wording "Net Zero Energy Building" focuses on the annual energy balance, large differences may occur between solution sets in the amount of grid interaction needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 7 publications
0
57
0
1
Order By: Relevance
“…However, as buildings are occupied it is also important to understand how the behavior and acceptance of the users of the buildings will influence the actual obtainable Energy Flexibility in buildings. The work will among others take offset in earlier work on flexibility indicators from the IEA SHC Task 40/EBC Annex 52 Towards Net Zero Energy Solar Buildings [3], [4] and [5].…”
Section: Subtask A: Definitions and Contextmentioning
confidence: 99%
“…However, as buildings are occupied it is also important to understand how the behavior and acceptance of the users of the buildings will influence the actual obtainable Energy Flexibility in buildings. The work will among others take offset in earlier work on flexibility indicators from the IEA SHC Task 40/EBC Annex 52 Towards Net Zero Energy Solar Buildings [3], [4] and [5].…”
Section: Subtask A: Definitions and Contextmentioning
confidence: 99%
“…11 shows, all the studied houses qualify to be classified as Energy Plus Buildings, if their final energy balance coincides with the estimated values. Indeed, being grid-connected houses, they could be classified as Net Energy Plus Buildings [9,10].…”
Section: Sde2012 Houses: Estimate Annual Energy Performancementioning
confidence: 99%
“…Since the SDE houses are grid connected, upon verifying that they comply with the ZEB requirement, they can be termed Net ZEB. In relation with Net ZEB, Voss et al [9,10] remark that this term is commonly used to describe the synergy between energy efficiency buildings and the renewable energy utilization to get an energy balance over an annual cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the application sites of renewable energy such as glazed balconies, solar walls, and solar collectors were analyzed through remodeling demonstration buildings evaluated between 1995 to 1998 [21]. In addition, the interaction between the building load matching and grid as a part of Subtask A of the Task 40/Annex 52 was analyzed through various case studies [22]. Among the NZEB cases, a study assessed the performance of the EcoTerra House in Canada, where it was found that its energy consumption was approximately 12.4% of that of regular Canadian homes [23][24][25].…”
Section: Introductionmentioning
confidence: 99%